Қазақстан Республикасындағы көшіп-қону үрдісін əкімшілік-құқықтық реттеу мəселелері - Ботағарин, Р.Б.; Мусин, Қ.Қ. (ҚарМУ басп., 2009)
В статье рассматриваются вопросы выезда и въезда иностранных граждан в Республику Ка- захстан, а также исследуются отношения, возникающие в сфере миграционных процессов, и некоторые проблемы административно-правового регулирования указанных правоотношений. In given article by author are considered questions of departure and entrance foreign people in Republic Kazakhstan, although as are researched relations, appearing in sphere of migrational processes and some problems of administrative-legal regulation specified on law relations.